Capacitance meter / Hishamuddin Mohd Shah - Mohd Shah, Hishamuddin (1992)
CAPACITANCE are among the most common components used in electronics today. The capacitance meter which I have constructed will be function well when all the construction is completed. Once the component is connected between the test terminal, the display will directly give the reading, without any help from external operator or switch apart from the power switch apart from the power switch. It can be used to measure both electrolytic and non-electrolytic capacitor. The range which can be measured by this meter is 10OpF for the minimum range and for the maximum range is 100mF.